Dispositivo intrauterino y embarazo en el Hospital de Apoyo Integrado II al IPSS – Tarapoto. Periodo 1980 – 1984 - Chung García, Fernando (1991)
10 case histories of accidental pregnancies occurred among 584 users of the IUD in the span of 1,980 and 1,984 were reviewed. Of these patients had inserted Cooper T 221, Lippes "C" 109 and 172 Lippes "D", 82 ignored. We found an incidence of 1.71% similar to that found by other authors pregnancies. 60 /. of pregnancies they occurred in patients between 21 and 30 years and the lowest 10%. between 41 years and more. The highest percentage of pregnancies occurred in users of Lipes "D", 60%. And during the first year of use, 70% .. The D.I.U. was in situ in 06 cases, GO'l., in one case I was expelled, 10%, and in 03 cases could not be precise location, 30% in 02 cases was not known how the pregnancy ended, 20%. In 08 cases, the pregnancy ended well: In 07 cases births; Term 05 cases, 50%, 02 cases preterm, 20%, 01 abortions case, 10%. and no cases of ectopic pregnancy did not. The children were all normal, There was no malformation